Identification of the mining accidents by a two-step clustering method for the mining-induced seismicity - Jian, Zheng; Zhao, Guoyan; Wang, Peicong; Liu, Xingquan; Jiang, Mingwei; Liu, Leilei; Ma, Ju (Frontiers in Earth Science, 2024)
Clustering methods aim to categorize data or samples into distinct groups based on their similarity.When applying clustering methods to earthquake events, it is crucial to establish a metric for quantifying the similarity between these events. Directly applying this clustering method to a catalog of mining-induced seismicity may lead to clustering earthquake events induced by different mining activities or accidents into the same group. To address this issue, a two-step clustering method has been proposed and applied for analyzing a catalog of mining-induced seismicity. The first step involves spatial distance-based clustering of seismic events, while the second step focuses on moment tensor analysis-based clustering of these events. The results obtained from the MT-based clustering method are visualized using Hudson Graphs, and box plots serve as an evaluation tool for assessing the quality of MT clustering. Most box plots demonstrate desirable quality in terms of MT cluster results, indicating successful outcomes. By the proposed two-step clustering method combined with actual mining activities, the potential accident locations and categories can be hypothesized while valuable recommendations provided for mining operations.